Emodin Improves Glucose and Lipid Metabolism Disorders in Obese Mice via Activating Brown Adipose Tissue and Inducing Browning of White Adipose Tissue - Cheng, Long; Zhang, Shuofeng; Shang, Fei; Ning, Yibo; Huang, Zhiqi; He, Runcheng; Sun, Jianning; Dong, Shifen (Frontiers in Endocrinology, 2021)
Background: Adipose tissue (e.g. white, brown and brite) plays a critical role in modulating energy metabolism. Activating brown adipose tissue (BAT) and inducing browning in white adipose tissue (WAT) has been proposed to a potential molecular target for obesity treatment. Emodin is a natural anthraquinone derivative that exhibited variety of pharmacologic effects including lowering lipids and regulating glucose utilization. However, the underlying mechanism of action is still not clear. In the present study, we investigated whether emodin could alleviate obesity via promoting browning process in adipose tissue. Methods: C57BL/6J mice were fed with high fat diet to induce obesity. Emodin at the doses of 40 and 80 mg/kg were orally given to obesity mice for consecutive 6 weeks. Parameters including blood lipids and adipose tissue morphology were assayed. Relative mRNA expression in scWAT was analyzed using qRT-PCR. Then the protein expression in scWAT and BAT were analyzed using western blotting. In addition, ultra-high-performance liquid chromatography with electrospray ionization tandem mass spectrometry was utilized to detect the small lipid metabolites of scWAT and BAT. Results: Emodin decreased the body weight and food intake in HFD-induced obesity mice, and it also improved the glucose tolerance and reduced the blood lipids. Emodin treatment induced beiging of scWAT, and more multilocular lipid droplets were found in scWAT. Also, emodin significantly increased markers of beige adipocytes, e.g. Cd137, Tmem26 and Tbx1 mRNA in scWAT, and UCP1, CD36, FATP4, PPARα and prohibitin protein expression in scWAT and BAT. Furthermore, emodin treatment perturbed the lipidomic profiles in scWAT and BAT of obese mice. Emodin increased Cer; LPC, LPC-O, and PE-O species concentration in scWAT, as well as PC and PE in BAT, when compared with HFD mice. Conclusions: These results indicated that emodin could ameliorate adiposity and improve metabolic disorders in obese mice. Also, emodin could promote browning in scWAT and activate the BAT. In addition, emodin treatment-induced changes to the scWAT and BAT lipidome were highly specific to certain molecular lipid species, indicating that changes in tissue lipid content reflects selective remodeling in scWAT and BAT of both glycerophospholipids and sphingolipids in response to emodin treatment.